Reduction in peak average power ratio for mimo-ofdm system - Pinardi, Sofia (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
Orthogonal frequency division multiplexing (OFDM) technology was adopted as the downlink and single-carrier FDMA (SC-FDMA) for uplink in the fourth-generation (4G) whereas as downlink and uplink transmission schemes for the fifth-generation (5G) communication systems. The high peak average power ratio (PAPR) value is of particular concern for all communication systems incorporating OFDM technology as their multiplexing and modulation methods. With cyclic prefixes, time-domain all the N subcarriers are added up constructively; they produce a peak power by systems incorporating OFDM, causing the increase of PAPR value. Reducing the PAPR has become a daunting task for developers of the 4G and 5G cellular communication systems. Due to the high PAPR value, the system requires exclusively higher power amplifiers (PA), increasing the systems' price. The main objective of the research is to assess and identify some techniques that can make up a system capable of experiencing the lowest possible overall PAPR value. The study's objectives are At this juncture, conventional OFDM systems use the transform algorithms, namely the inverse fast Fourier transform (IFFT) and fast Fourier transform (FFT), in the transmit and receive side, respectively. The research objective also includes investigating the number of subcarriers used and its effect on the PAPR value. Another objective is to determine which transform algorithm, including its associated family, experiences the lowest PAPR value and inspect what type of modulation experienced the lowest PAPR value. The study also examines the best multiple-input multiple-output (MIMO) antenna diversity configuration and observes the effect on several channel model conditions. The research methodology entails the replacement of the conventional transform algorithm inverse discrete Fourier transform (IDFT) and discrete Fourier transform (DFT) with inverse discrete Wavelet transform (IDWT) and discrete Wavelet transform (DWT) in the transmitter and receiver, respectively. Similar assessments had also been carried out for the discrete cosine transform (DCT) algorithm. Most members of the Wavelet family had been inspected. Three variations of the subcarrier, namely 64, 128, and 256, had been appraised. The PAPR values were thoroughly assessed based on five modulations: the QPSK, 8-PSK, 16-QAM, 32-QAM, and 64-QAM. The research undertakings also encompass PAPR value determination observed at the receiver involving MIMO antenna configurations. Three configurations, such as MIMO 2x2, MIMO 4x4, and MIMO 8x8, had been examined. Also, three channel-model conditions, such as AWGN+Rayleigh, AWGN+Rician, and AWGN+Nakagami, were evaluated. All simulations in determining the PAPR values were carried out using pseudocode and MATLAB programming language. This study can observe that a lower number of subcarriers instigates a lower PAPR value. It can be concluded that the deployment of transform algorithm 'bior 1.1' of the Wavelet family and 16-QAM modulation with 64 subcarriers and MIMO 4x4 are the best configuration capable of establishing the lowest PAPR values. The application of MIMO somehow did not exhibit a significant reduction of PAPR values. The overall results imply that a Wavelet-based OFDM system with QAM modulation and MIMO-OFDM will experience the lowest PAPR value. In a nutshell, it had been identified that a PAPR value of 6.77 dB lower than a conventional OFDM system could be established at the transmitter, whereas a PAPR value of 3.62 dB lower can be formed at the receiver.